(untitled) (Latakia University Journal -Basic Sciences Series, 2014)
تناول هذا البحث دراسة تأثير أهم العوامل في المنحنيات الفولط أمبيرومترية للرصاص والنحاس , للوصول إلى الشروط المثلى للتحديد المتزامن لهذين العنصرين , بالطريقة الفولط أمبيرومترية التراكمية الأنودية النبضية التفاضلية DPASV))، وباستخدام مسرى قطرة الزئبق المعلقة(HMDE) بصفة مسرى عامل. أظهرت النتائج أن الشروط المثلى للتحديد المتزامن للرصاص، والنحاس كانت عند استخدام كهرليت من حمض الأزوت بتركيز ، بتطبيق مجال مسح كموني من إلى+150 عند كمون تراكم ، وزمن تراكم 80 sec، وسرعة مسح 40 mV/sec، وسعة نبضة 70 mV، حيث كانت قيم تيار القمة للرصاص ، ، عند كمونات قمّة ، وبتطبيق هذه الشروط تم التوصل لحدود كشف 1.05 μg/l للرصاص, و2.45 μg/l للنحاس، وحسبت الاسترجاعية للتأكد من صحة الطريقة، إذ كانت للرصاص 103.90%، وللنحاس 101.70%¬¬¬¬¬¬¬¬، ولبيان دقة الطريقة بحسب الانحراف المعياري , فكان 0.027mg/l للرصاص, و0.013mg/l للنحاس ، طبقت الطريقة بشروطها المختارة على بعض العيّنات الواقعية فأبدت نجاحاً وكفاءة عالية. This research study the effect of the most important conditions on the voltammetric curves of lead and copper to reach the optimal conditions for the simultaneous determination of these elements by Differential pulse anodic stripping voltammetry (DPASV) using a hanging mercury drop electrode (HMDE) as a working electrode. The results showed that the optimal conditions for the simultaneous determination of lead and copper by using nitric acids electrolyte 3M,were when applying scanning field from -700 mV to +150 mV, accumulation potential -800 mV, the time of the accumulation 80 sec, speed rate 40 mV/sec, and the amplitude pulse 70mV, where the peak currents were IP (Pb) = 274.2 nA, IP (Cu) = 630.5 nA, at peak potentials EP (Pb) = -380 mV, EP (Cu) = +40 mV, by applying the previous conditions, the limits of detection reached 1.05μg/l for lead 2.45 μg/l for copper. The retrieval coefficient calculated to make sure accuracy of the method and it reached 103.90% and copper 101.70% and to indicate the precision of the way by the standard deviation was the value of the standard deviation for lead 0.027 mg/l, and copper 0.013 mg/l. the method applied under its own conditions by examined on some of environmental and samples and showed success and high efficiency